Preserving Cultural Diversity in Rural Africa Using Renewable Energy - Roduner, Emil; Rohwer, Egmont R. (Global challenges, 2024)
Ninety percent of the large interior, rural part of Africa is not an abundant user of fossil fuels and is not connected to an electricity grid. This limits habitability and leads to significant migration to larger cities in attempts to improve economic and social welfare, which happens at the cost of its rich cultural diversity by inevitable adaption and mixing of societies. A direct transition from a firewood to an off‐grid renewable electricity age can mitigate this detrimental development. This perspective discusses the interdisciplinary requirements linking cultural, sociological, economic, and technical aspects for a transition to modern life without loss of valuable traditions. Photovoltaic power and wind energy can provide local affordable electricity in off‐grid locations. Intermediate storage for day–night cycles is catered for by novel types of batteries. Purifying and recycling water, refrigerating food and medicine, and benefitting from contact with the world via electronic media permit a tremendous increase in living conditions and significantly lower the pressure of migration into cities. Access to energy is a fundamental requirement for the preservation of the rich cultural diversity with family and tribal bindings, local languages, traditions, and religions, and allows for a more moderate transition to a modern society. Renewable energy can provide the missing electricity in the large off‐grid part of Sub‐Saharan Africa. This leads to tremendously improved habitability and preserves the rich cultural diversity. The main benefit relates to securing jobs, refrigeration of food and medicine, purifying and recycling water, and connecting to the world via electronic media.